Kohlbergian analysis of the moral reasoning in Lino Brocka's leading films - Palmes, Diana F. (Humanities Diliman, 2015)
The year 2014 marks the 75th birth anniversary of the Filipino film maker and National Artist for Film Lino Brocka. By using the moral development theory of the American psychologist Lawrence Kohlberg, this paper examines sixteen cases of moral dilemmas and their resolutions, as found in Brocka’s iconic films Tinimbang Ka Ngunit Kulang (You’ve Been Weighed and Found Wanting), Maynila sa mga Kuko ng Liwanag (Manila, In the Claws of Light), Insiang, Jaguar (Guard), Bayan Ko: Kapit sa Patalim (My Country: Gripping the Knife’s Edge), and Orapronobis (Fight for Us). This paper established that one of the techniques that Brocka used in his moral discourses is to contrast the moral reasoning of his f ictive agents with his own moral reasoning. This results in an infusion of his moral narratives with the potentiality for multiple interpretation by the audience: in some cases, this contrapuntal technique was used to propose a third higher moral narrative; while in others, the moral narratives of Brocka had the tendency to challenge the Philippine traditional norms and rules, as well as the hypocrisies of the Philippine society; and finally, that Brocka tended to intertwine his moral and political discourses, particularly his argument for class solidarity as the remedy of the injustices brought about by the power inequality among Philippine social classes. Thus, Brocka’s masterpieces should not only be used as materials in the study of Philippine films, or in the study of political and social criticism; but more so as materials for the study of ethics and morality that are relevant to Philippine social conditions.